Electrochemical devices and electronic devices

CN116391284BActive Publication Date: 2026-10-30NINGDE AMPEREX TECHNOLOGY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280007185.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-28
Publication Date
2026-10-30
Estimated Expiration
2042-03-28

AI Technical Summary

Technical Problem

[0003]以锂离子电池为例,常使用具有较高克容量的天然石墨作为负极材料,但天然石墨的大片层多孔结构使其难以兼具优异的循环性能及动力学性能,限制了天然石墨在高性能的电化学装置中的应用

Benefits of technology

[0017]本申请提供的电化学装置的负极包括特定的负极活性材料层,使得电化学装置在具有高容量的同时,兼具优异的循环性能及动力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided is an electrochemical device including a negative electrode including a negative electrode current collector and a negative electrode active material layer including a negative electrode active material, wherein the negative electrode active material layer satisfies 0.1 ≤ SA / S002 ≤ 0.3, SA is a peak area value of an A peak in an XRD pattern of the negative electrode active material layer in a range of 42.4° to 43.6°, and S002 is a peak area value of a 002 peak in the XRD pattern of the negative electrode active material layer. The electrochemical device of the present application has high gravimetric capacity, excellent cycle performance, and kinetic performance. An electronic device including the electrochemical device is also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of energy storage, specifically to an electrochemical device and an electronic device. Background Technology

[0002] Electrochemical devices such as lithium-ion batteries have already gained a mainstream position in the market due to their outstanding advantages, including high energy density, high safety, no memory effect, and long operating life. With the increasing popularity of consumer electronics products such as laptops, mobile phones, tablets, power banks, and drones, the requirements for their electrochemical devices are becoming increasingly stringent. For example, batteries are not only required to be lightweight, but also to have high capacity and a long operating life.

[0003] Taking lithium-ion batteries as an example, natural graphite with high specific capacity is often used as the negative electrode material. However, the large-sheet porous structure of natural graphite makes it difficult to have both excellent cycle performance and kinetic performance, which limits the application of natural graphite in high-performance electrochemical devices. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this application provides an electrochemical device and an electronic device including the electrochemical device. The electrochemical device of this application possesses high specific capacity while also exhibiting excellent cycle performance and kinetic performance.

[0005] In a first aspect, this application provides an electrochemical device comprising a negative electrode, which includes a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer comprises a negative electrode active material, wherein the negative electrode active material layer satisfies 0.1 ≤ SA / S002 ≤ 0.3, where SA is the peak area of ​​the A peak in the XRD pattern of the negative electrode active material layer within the range of 42.4° to 43.6°, and S002 is the peak area of ​​the O02 peak in the XRD pattern of the negative electrode active material layer. The peak area SA of the A peak of the negative electrode active material layer is negatively correlated with the thickness of the active material layer. A larger SA indicates a smaller thickness of the negative electrode active material layer, making it easier for active metal ions such as lithium ions to be inserted and extracted in the negative electrode active material layer, but the energy density of the electrochemical device will decrease. The peak area value S002 of the 002 peak in the negative electrode active material layer is related to the amount of active metal ions, such as lithium ions, that can be intercalated in the negative electrode active material. The larger the S002, the greater the amount of active metal ions that can be intercalated, which is beneficial to improving the energy density of the electrochemical device. However, if the S002 is too large, the deformation of the electrochemical device will increase. After extensive research, the inventors of this application found that when SA / S002 is controlled within the above range, both the energy density of the electrochemical device and the normal intercalation and deintercalation of active metal ions in the active material can be guaranteed. The electrochemical device has both high specific capacity and excellent cycle performance and kinetic performance.

[0006] According to some embodiments of this application, 7000 ≤ SA ≤ 9000. According to some embodiments of this application, 25000 ≤ S002 ≤ 90000. In this application, SA value is the peak area of ​​peak A in the XRD pattern of the negative electrode active material layer when the electrochemical device is in a fully discharged state. S002 value is the peak area of ​​peak 002 in the XRD pattern of the negative electrode active material layer when the electrochemical device is in a fully discharged state.

[0007] According to some embodiments of this application, the half-width at half-maximum (WHM) of peak A is 0.1° to 0.5°. The WHM of peak A reflects the thickness of the active material layer. The narrower the WHM, the smaller the thickness of the active material layer, which is beneficial for the intercalation of active metal ions into the active material layer and improves the kinetic performance of the electrochemical device.

[0008] According to some embodiments of this application, in the XRD pattern of the negative electrode active material layer, 2θ has a 101 peak in the range of 43.6° to 46.6°, where 0.015≤S101 / S002≤0.035, and S101 is the peak area value of the 101 peak.

[0009] According to some embodiments of this application, the full width at half maximum (FWHM) of the 101 peak is 0.3° to 0.8°. The 101 peak is related to the amount of active metal ions that can be intercalated in the active material. The greater the peak intensity and the narrower the FWHM of the 101 peak, the greater the amount of active metal ions that can be intercalated. Therefore, controlling the peak intensity and FWHM of the 101 peak within a certain range is beneficial to obtaining a negative electrode active material with a high amount of intercalated active metal ions, thereby increasing the specific capacity of the active material.

[0010] According to some embodiments of this application, the negative current collector is copper foil.

[0011] According to some embodiments of this application, the negative electrode current collector contains chromium, with a chromium content of 0.008% to 0.020% based on the mass of the negative electrode current collector. According to some embodiments of this application, the negative electrode current collector contains niobium, with a niobium content of 0.005% to 0.009% based on the mass of the negative electrode current collector. According to some embodiments of this application, the negative electrode current collector contains sulfur, with a sulfur content of 0.001% to 0.006% based on the mass of the negative electrode current collector. Controlling the content of trace elements in the current collector can facilitate the extension of the negative electrode active material during the deintercalation / intercalation of active metal ions, thereby suppressing the deformation of the electrochemical device and improving the kinetic and cycle performance of the electrochemical device.

[0012] According to some embodiments of this application, the thickness of the negative electrode active material layer is H μm, where 87 ≤ SA / H ≤ 300. In some embodiments, the thickness of the negative electrode active material layer is H μm, and the weight of the negative electrode active material layer per unit area is C g / cm³. 2Where 0.003≤C≤0.01, 1.0≤10 4 ×C / H ≤ 1.7. SA is inversely proportional to the thickness of the active material. Generally, the smaller the H of the active material layer, the larger the SA, which translates to a faster rate of intercalation of active metal ions and less lithium deposition. However, if the thickness of the active material layer is too small, under the same active material layer weight (C g / cm³),... 2 (Similarly), the greater the pressure applied to the electrode, the more difficult it is for active metal ions to intercalate into the active material layer, resulting in a higher internal resistance of the electrochemical device. Therefore, controlling the thickness of the active material layer and the weight of the negative electrode active material layer per unit area within the aforementioned range is beneficial for controlling the intercalation and deintercalation rates of active metal ions, improving the specific capacity of the negative electrode active material, and enhancing the cycle performance and kinetic performance of the electrochemical device.

[0013] According to some embodiments of this application, the negative electrode active material layer satisfies 10 ≤ S004 / S110 ≤ 25, where S004 is the peak area of ​​the 004 peak in the XRD pattern of the negative electrode active material layer, and S110 is the peak area of ​​the 110 peak in the XRD pattern of the negative electrode active material layer. When the ratio of S004 / S110 is within the above range, the internal resistance of active metal ion insertion / extraction from the negative electrode active material is small, and the deposition of active metal ions can be reduced, thereby improving the cycle performance and kinetic performance of the electrochemical device.

[0014] According to some embodiments of this application, the negative electrode active material comprises natural graphite. In some embodiments, the specific surface area (BET) of the negative electrode active material is 2 g / cm³. 2 Up to 5 g / cm 2 In some embodiments, the specific capacity of the negative electrode active material is 360 mAh / g to 370 mAh / g.

[0015] In some embodiments, the particle size of the negative electrode active material satisfies 1μm≤Dv10≤10μm, 3μm≤Dv50≤18μm, and 8μm≤Dv90≤35μm. When the particle size distribution of the negative electrode active material is within the above range, it can ensure that the internal resistance of the active metal ion insertion / extraction from the negative electrode active material is small, the deposition of active metal ions is reduced, and the side reactions with the electrolyte are reduced, thus ensuring that the electrochemical device has better cycle performance and kinetic performance.

[0016] In a second aspect, this application provides an electronic device that includes the electrochemical device of the first aspect.

[0017] The negative electrode of the electrochemical device provided in this application includes a specific negative electrode active material layer, which enables the electrochemical device to have high capacity while also having excellent cycle performance and kinetic performance. Detailed Implementation

[0018] The present application will be further described below with reference to specific embodiments. It should be understood that these specific embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0019] I. Electrochemical Device In a first aspect, this application provides an electrochemical device comprising a negative electrode, the negative electrode comprising a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer comprising a negative electrode active material, wherein the negative electrode active material layer satisfies 0.1≤SA / S002≤0.3, SA is the peak area value of the A peak in the XRD pattern of the negative electrode active material layer in the range of 42.4° to 43.6°, and S002 is the peak area value of the 002 peak in the XRD pattern of the negative electrode active material layer.

[0020] In this application, the characteristic peak of 2θ in the XRD pattern of the negative electrode active material layer in the range of 25.0° to 27.0° is the 002 peak.

[0021] In some embodiments, SA / S002 is a range of 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, or any combination of these values. The peak area SA of peak A in the negative electrode active material layer is negatively correlated with the thickness of the active material layer. The larger the SA, the smaller the thickness of the negative electrode active material layer, and the easier it is for active metal ions to be inserted and extracted in the negative electrode active material layer, but the energy density of the electrochemical device will decrease. The peak area value S002 of the 002 peak in the negative electrode active material layer is related to the amount of active metal ions, such as lithium ions, that can be intercalated in the negative electrode active material. The larger the S002, the greater the amount of active metal ions that can be intercalated, and the greater the specific capacity of the negative electrode active material, which is beneficial to improving the energy density of the electrochemical device. However, when S002 is too large, the deformation rate of the electrochemical device increases, affecting its kinetic performance. After extensive research, the inventors of this application discovered that when SA / S002 is controlled within the above-mentioned range, both the energy density of the electrochemical device and the normal intercalation and deintercalation of active metal ions in the active material can be guaranteed. The electrochemical device has both high specific capacity and excellent cycle performance and kinetic performance.

[0022] According to some embodiments of this application, 7000 ≤ SA ≤ 9000. In some embodiments, SA is a range of 7100, 7300, 7500, 7700, 7900, 8000, 8100, 8300, 8500, 8700, 8900, or any combination of these values. According to some embodiments of this application, 25000 ≤ S002 ≤ 90000. In some embodiments, S002 is a range of 27000, 30000, 34000, 40000, 45000, 50000, 55000, 60000, 65000, 70000, 75000, 80000, 85000, or any combination of these values. In this application, the SA value is the peak area of ​​peak A in the XRD pattern of the negative electrode active material layer when the electrochemical device is in a fully discharged state. The S002 value is the peak area of ​​the 002 peak in the XRD pattern of the negative electrode active material layer when the electrochemical device is in a fully discharged state.

[0023] According to some embodiments of this application, the half-width at half-maximum (WHM) of peak A is 0.1° to 0.5°. In some embodiments, the WHM of peak A is a range of 0.15°, 0.17°, 0.2°, 0.23°, 0.25°, 0.27°, 0.3°, 0.33°, 0.35°, 0.37°, 0.4°, 0.43°, 0.45°, 0.47°, or any combination of these values. The WHM of peak A reflects the thickness of the active material layer. A narrower WHM indicates a smaller active material layer thickness, which is beneficial for the intercalation of active metal ions into the active material layer and improves the kinetic and cycling performance of the electrochemical device.

[0024] According to some embodiments of this application, in the XRD pattern of the negative electrode active material layer, 2θ has 101 peaks in the range of 43.6° to 46.6°, where 0.015 ≤ S101 / S002 ≤ 0.035, and S101 is the peak area value of the 101 peaks. In some embodiments, S101 / S002 is a range of 0.017, 0.019, 0.02, 0.021, 0.023, 0.025, 0.027, 0.029, 0.030, 0.031, 0.033, or any combination of these values.

[0025] According to some embodiments of this application, the half-width at half-maximum (WHM) of the 101 peak is 0.3° to 0.8°. In some embodiments, the WHM of the 101 peak is a range of 0.35°, 0.37°, 0.4°, 0.43°, 0.45°, 0.47°, 0.5°, 0.53°, 0.55°, 0.57°, 0.6°, 0.63°, 0.65°, 0.67°, 0.7°, 0.73°, 0.75°, 0.77°, or any combination of these values. The 101 peak is related to the amount of active metal ions that can be intercalated in the active material. The greater the peak intensity and the narrower the WHM of the 101 peak, the greater the amount of active metal ions that can be intercalated. Therefore, controlling the peak intensity and WHM of the 101 peak within a certain range is beneficial for obtaining a negative electrode active material with a high amount of intercalated active metal ions, resulting in a negative electrode active material with a high specific capacity.

[0026] According to some embodiments of this application, the negative current collector is copper foil.

[0027] According to some embodiments of this application, the negative electrode current collector contains chromium, and the chromium content is from 0.008% to 0.020% based on the mass of the negative electrode current collector, for example, 0.009%, 0.01%, 0.011%, 0.012%, 0.013%, 0.014%, 0.015%, 0.016%, 0.017%, 0.018%, 0.019%, or any combination of these values. According to some embodiments of this application, the negative electrode current collector contains niobium, and the niobium content is from 0.005% to 0.009% based on the mass of the negative electrode current collector, for example, 0.0055%, 0.006%, 0.0065%, 0.007%, 0.0075%, 0.008%, 0.0085%, or any combination of these values. According to some embodiments of this application, the negative electrode current collector contains sulfur. Based on the mass of the negative electrode current collector, the sulfur content is from 0.001% to 0.006%, such as 0.0015%, 0.002%, 0.0025%, 0.003%, 0.0035%, 0.004%, 0.0045%, 0.005%, 0.0055%, or any combination of these values. Controlling the content of trace elements in the current collector can facilitate the extension of the negative electrode active material during the lithium insertion / extraction process, thereby suppressing the deformation of the electrochemical device and improving the kinetic and cycle performance of the electrochemical device.

[0028] According to some embodiments of this application, the thickness of the negative electrode active material layer is H μm, where 87 ≤ SA / H ≤ 300. In some embodiments, the thickness of the negative electrode active material layer is H μm, and the weight of the negative electrode active material layer per unit area is C g / cm³. 2 Where 0.003≤C≤0.01, 1.0≤104 ×C / H ≤ 1.7. SA is inversely proportional to the thickness of the active material. Generally, the smaller the H of the active material layer, the larger the SA. This translates to a faster rate of insertion and extraction of active metal ions, making them less prone to deposition. However, if the thickness of the active material layer is too small, under the same active material layer weight (C g / cm³),... 2 (Similarly), the greater the pressure applied to the electrode, the more difficult it is for active metal ions, such as lithium ions, to intercalate into the active material layer, resulting in increased intercalation resistance. Therefore, controlling the thickness of the active material layer and the weight of the negative electrode active material layer per unit area within the aforementioned range is beneficial for controlling the intercalation and deintercalation rates of active metal ions, improving the specific capacity of the negative electrode active material, and enhancing the kinetic and cycle performance of the electrochemical device.

[0029] According to some embodiments of this application, the negative electrode active material layer satisfies 10 ≤ S004 / S110 ≤ 25, where S004 is the peak area of ​​the 004 peak in the XRD pattern of the negative electrode active material layer, and S110 is the peak area of ​​the 110 peak in the XRD pattern of the negative electrode active material layer. In some embodiments, S004 / S110 is a range of 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or any combination of two of these values. The S004 / S110 ratio is related to the particle size of the negative electrode active material. When the particle size of the negative electrode active material decreases, the S004 / S110 ratio decreases accordingly. At this time, the internal resistance of active metal ions intercalating / deintercalating into the negative electrode active material is small, and the deposition of active metal ions can be reduced. This can reduce the internal resistance of the electrochemical device and improve the capacity retention rate of the electrochemical device under high-rate charge and discharge conditions. When the S004 / S110 ratio meets the above range, the electrochemical device has a low internal resistance and a high capacity retention rate under high-rate charge and discharge conditions. The electrochemical device has better kinetic performance and cycle performance.

[0030] According to some embodiments of this application, the negative electrode active material comprises natural graphite. In some embodiments, the specific surface area (BET) of the negative electrode active material is 2 g / cm³. 2 Up to 5 g / cm 2 For example, 2g / cm 2 2.5g / cm 2 3g / cm 2 3.5g / cm 2 4g / cm 2 4.5g / cm 2 Or a range of any two of these values. In some embodiments, the specific capacity of the negative electrode active material is from 360 mAh / g to 370 mAh / g.

[0031] In some embodiments, the particle size of the negative electrode active material satisfies 1μm≤Dv10≤10μm, 3μm≤Dv50≤18μm, and 8μm≤Dv90≤35μm. In this application, Dv10 represents that 10% of the particles in the volumetric particle size distribution of the negative electrode active material are smaller than this value. Dv50 represents that 50% of the particles in the volumetric particle size distribution of the negative electrode active material are smaller than this value. Dv90 represents that 90% of the particles in the volumetric particle size distribution of the negative electrode active material are smaller than this value.

[0032] In some embodiments, Dv10 is a range of 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, or any combination of these values. In some embodiments, Dv50 is a range of 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, or any combination of these values. In some embodiments, Dv90 is a range of 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 26μm, 28μm, 30μm, 32μm, 34μm, or any combination of these values. As the particle size of the negative electrode active material decreases, the S004 / S110 ratio also decreases accordingly. At this point, the internal resistance of active metal ions intercalating / deintercalating in the negative electrode active material is smaller, and the deposition of active metal ions is reduced. This can lower the internal resistance of the electrochemical device and improve the capacity retention rate of the electrochemical device during high-rate charge and discharge. However, if the particle size of the negative electrode active material is too small, the specific surface area of ​​the negative electrode active material is too large, and the contact area with the electrolyte increases, which can easily trigger side reactions with the electrolyte. This reduces the initial efficiency of the electrochemical device during the first intercalation / deintercalation of active metal ions. Therefore, it is necessary to control it within a certain range to ensure that the electrochemical device has better performance.

[0033] The electrochemical device of this application also includes a positive electrode, which includes a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer including a positive electrode active material, a binder and a conductive agent.

[0034] According to some embodiments of this application, the positive current collector can be a metal foil or a composite current collector. For example, aluminum foil can be used. The composite current collector can be formed by forming a metallic material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer substrate.

[0035] According to some embodiments of this application, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel-type lithium manganese oxide, spinel-type lithium nickel manganese oxide, and lithium titanate. In some embodiments, the binder includes at least one of adhesive polymers, such as polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified SBR rubber, or polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyenol, or polyacrylic acid. In some embodiments, the conductive agent includes carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, or carbon fiber; metal-based materials, such as metal powder or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof.

[0036] The electrochemical device of this application also includes a separating membrane. The material and shape of the separating membrane used in the electrochemical device of this application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separating membrane comprises a polymer or inorganic material formed from a material stable to the electrolyte of this application.

[0037] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, membrane, or composite membrane with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be selected.

[0038] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixture of polymer and inorganic material. The inorganic layer includes inorganic particles and a binder. The inorganic particles are selected from at least one of alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of polyvinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl alkoxy, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene. The polymer layer contains a polymer, and the polymer material is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl alkoxy, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0039] The electrochemical device of this application also includes an electrolyte. The electrolyte that can be used in this application can be any electrolyte known in the prior art.

[0040] According to some embodiments of this application, the electrolyte includes an organic solvent, a lithium salt, and optional additives. The organic solvent in the electrolyte of this application can be any organic solvent known in the prior art that can be used as an electrolyte solvent. There are no limitations on the electrolyte used in the electrolyte of this application; it can be any electrolyte known in the prior art. The additives in the electrolyte of this application can be any additives known in the prior art that can be used as electrolyte additives. In some embodiments, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, or ethyl propionate. In some embodiments, the organic solvent includes ether solvents, such as at least one selected from 1,3-dioxane (DOL) and dimethyl glycol ether (DME). In some embodiments, the lithium salt includes at least one selected from organic lithium salts or inorganic lithium salts. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate)borate LiB(C2O4)2 (LiBOB), or lithium difluorooxalatoborate LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.

[0041] According to some embodiments of this application, the electrochemical device of this application includes, but is not limited to, a lithium-ion battery or a sodium-ion battery. In some embodiments, the electrochemical device is a lithium-ion battery.

[0042] II. Electronic Devices This application further provides an electronic device that includes the electrochemical device described in the first aspect of this application.

[0043] The electronic devices or apparatus described in this application are not particularly limited. In some embodiments, the electronic devices described in this application include, but are not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.

[0044] Unless otherwise specified, all reagents, materials and instruments used in the following examples and comparative examples are commercially available.

[0045] Examples and Comparative Examples Preparation of positive electrode The positive electrode active material lithium cobalt oxide (molecular formula LiCoO2), the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are thoroughly mixed in an appropriate amount of N-methylpyrrolidone (NMP) solvent at a weight ratio of 96:2:2 to form a uniform positive electrode slurry. This slurry is then coated onto a current collector aluminum foil, dried, cold-pressed, cut into sheets, and the tabs are welded to obtain the positive electrode.

[0046] Preparation of negative electrode Preparation of negative electrode active material: Natural graphite ore is selected, crushed / ball-milled, and flotated to obtain natural flake graphite. The natural flake graphite is crushed, preferably to a particle size Dv50 of 3μm to 18μm, and then spheroidized to obtain material A. Material A is mixed with a certain amount of coating agent in a mixing ratio of 50:50 to 90:10. After uniform mixing, it is placed in a high-temperature carbonization furnace and calcined at 1150℃ for 4 hours to obtain material B. Material B is the negative electrode active material graphite used in the experiment. The coating agent is a mixture of 50% to 90% solvent and 10% to 50% carbon material. The solvent includes toluene, ethanol, quinoline, or diethyl ether, and the carbon material includes carbon nanotubes or graphene.

[0047] The negative electrode active material, styrene-butadiene rubber (SBR) binder, and sodium carboxymethyl cellulose (CMC) thickener are thoroughly mixed in deionized water solvent at a weight ratio of 95:2:3 to form a uniform negative electrode slurry. This slurry is then coated onto a current collector copper foil pre-coated with a base coating (carbon black) with a thickness of 1.5 μm. After drying, the coated negative electrode is cold-pressed, cut, and welded using different roller pressures.

[0048] In the embodiments and comparative examples of this application, the peak values ​​and peak area values ​​in the XRD spectrum of the active material layer are adjusted by adjusting the particle size of the pulverized material and the type and content of the coating agent.

[0049] Preparation of electrolyte In a dry argon atmosphere, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) (weight ratio 1:1:1) are mixed uniformly to form a base solvent. Dry lithium salt LiPF6 is added to the base solvent and mixed uniformly. Then, fluoroethylene carbonate and adiponitrile are added and mixed uniformly to obtain the electrolyte. Based on the mass of the electrolyte, the mass content of fluoroethylene carbonate is 3%, the mass content of adiponitrile is 2%, the mass content of LiPF6 is 12.5%, and the remainder is the base solvent.

[0050] Preparation of the separating membrane A 7 μm thick porous polyethylene polymer film was used as the separator.

[0051] Preparation of lithium-ion batteries The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes. Then, they are wound, placed in an outer packaging foil, and injected with the prepared electrolyte. After vacuum sealing, settling, formation, and shaping processes, a lithium-ion battery is obtained.

[0052] Test methods 1. X-ray powder diffraction (XRD) test The testing method for the (002, 101, A) crystal plane diffraction peaks (hereinafter referred to as "002 peak, 101 peak, and A peak"): X-ray powder diffractometer (XRD, instrument model: Bruker D8 ADVANCE) was used to test the negative electrode active material layer, obtaining XRD test curves. The target material was Cu Kα, the voltage / current was 40 kV / 40 mA, the scanning angle range was 5° to 80°, the scanning step size was 0.00836°, and the step time was 0.3 s. The A peak is located at a diffraction angle of 2θ ranging from 42.4° to 43.6°, the 002 peak is located at a diffraction angle of 2θ ranging from 25.0° to 27.0°, and the 101 peak is located at a diffraction angle of 2θ ranging from 43.6° to 46.6°. S002, S101, and SA are the peak area values ​​obtained by integrating the 002 peak, 101 peak, and A peak, respectively.

[0053] Test method for S004 / S110: The (004) plane diffraction pattern and (110) plane diffraction pattern of the negative electrode active material layer were tested according to the People's Republic of China Machinery Industry Standard JB / T 4220-2011 "Method for Determination of Lattice Parameters of Artificial Graphite". The test conditions are as follows: CuKα radiation was used for X-rays, and CuKα radiation was removed by a filter or monochromator. The working voltage of the X-ray tube was (30-35) kV and the working current was (15-20) mA. The scanning speed of the counter was 1 / 4 (°) / min. Among them, the diffraction peak of the (004) plane (004 peak in the XRD pattern of the negative electrode active material layer) is located in the range of 52°-57° at the diffraction angle 2θ, and the diffraction peak of the (110) plane (110 peak in the XRD pattern of the negative electrode active material layer) is located in the range of 75°-80° at the diffraction angle 2θ. The peak area of ​​peak 004 is calculated by integration and denoted as S004, and the peak area of ​​peak 110 is calculated by integration and denoted as S110. The ratio of S004 / S110 of the negative electrode active material layer is then calculated.

[0054] In this application, the peak area values ​​of the 002 peak, 101 peak, A peak, 110 peak and 004 peak in the XRD pattern of the negative electrode active material layer represent the numerical values ​​of the peak area calculated from the XRD pattern.

[0055] 2. Particle size testing of negative electrode active materials A certain amount of negative electrode active material layer was taken, and the binder and thickener were removed by dissolving it with an organic solvent. After drying, negative electrode active material powder was obtained. 1g of negative electrode active material powder was taken and dissolved in dispersant water. The mixture was sonicated for 5 minutes at an ultrasonic intensity of 53KHz. The mixed suspension was then injected into a Malvern 3000 testing device. Each sample was tested three times, and the average value of the tests was taken to obtain the values ​​of Dv10, Dv50 and Dv90.

[0056] 3. Elemental analysis test Weigh 0.5g of copper foil from the negative electrode empty foil region. Mix the copper foil with 10mL of HNO3 solution. Dissolve the trace elements in the current collector in the solution using microwave digestion. Introduce the digested solution into an ICP light source. Use an inductively coupled plasma optical emission spectrometer (ICP-OES) to detect the content of different substances based on the characteristic radiation energy emitted when the outer electrons of gaseous atoms in the sample return from the excited state to the ground state after excitation.

[0057] 4. Gram capacity test (1) Preparation of button cell: The negative electrode is prepared using the negative electrode active material prepared in the above embodiment. The prepared negative electrode, lithium sheet, separator, electrolyte, steel sheet, nickel foam and button cell case are assembled together to obtain a button cell. The cell is left to stand for 6 hours before testing.

[0058] (2) Testing procedure for button cell: The assembled button cell is placed on a Blue Electric Tester for testing. The testing procedure is to discharge at 0.05C to the lower limit voltage of 5mV, discharge at 50μA to 5mV, let stand for 5min, charge at 0.1C to the upper limit voltage of 2.0V, let stand for 5min, and record the specific capacity at this time as the specific capacity of the negative electrode active material.

[0059] 5. BET test The specific surface area was tested according to GB / T 19587-2017. A certain amount of negative electrode active material layer was taken, and the binder and thickener were removed by dissolving it with an organic solvent. After drying, the negative electrode active material powder was obtained. The specific procedure was as follows: 1g to 8g of negative electrode active material (the sample weighing should at least cover 1 / 3 of the sphere volume) was placed in a 1 / 2-inch long tube with a bulb (the diameter of the spherical part of the tube was 12mm). After pretreatment at 200℃ for 2h, the sample was placed in the TriStar3030 testing equipment (McClone Systems, Inc., USA) for testing. The adsorbed gas used was N2 (purity: 99.999%). The test conditions were carried out at 77K, and the specific surface area was calculated by the BET calculation method.

[0060] 6. Lithium plating degree test of negative electrode sheet The lithium-ion battery under test was placed at 0℃ and allowed to stand for 5 minutes. It was then charged at a constant current of 0.7C to 4.45V, followed by constant voltage charging at 4.45V to 0.05C. After standing for 5 minutes, it was discharged at a constant current of 0.5C to 3.0V, and then allowed to stand for 5 minutes. This charge-discharge process was repeated 10 times. The battery was then fully charged, disassembled in a drying room, and the state of the negative electrode was photographed and recorded.

[0061] Lithium plating degree determination: The determination is based on the state of the negative electrode obtained from a fully charged disassembled battery. If the negative electrode is generally golden yellow and the area of ​​gray is less than 2%, it is determined to be no lithium plating; if the negative electrode is mostly golden yellow, but some areas are gray, and the gray area is between 2% and 20%, it is determined to be slight lithium plating; if the negative electrode is partially gray, but some golden yellow can still be observed, and the gray area is between 20% and 60%, it is determined to be lithium plating; if the negative electrode is mostly gray and the gray area is greater than 60%, it is determined to be severe lithium plating.

[0062] 7. DC Resistance (DCR) Test At 25ºC, the lithium-ion battery was charged at a constant current of 1.5C to 4.45V, then charged at a constant voltage of 4.45V to 0.05C, and left to stand for 30 minutes. It was then discharged at 0.1C for 10 seconds, and the voltage value was recorded as U1. Finally, it was discharged at 1C for 360 seconds, and the voltage value was recorded as U2. This charge-discharge cycle was repeated 5 times. "1C" refers to the current value required to completely discharge the lithium-ion battery within one hour.

[0063] The DC resistance R of a lithium-ion battery at 25ºC can be calculated using the following formula: R=(U2-U1) / (1C-0.1C).

[0064] The method described above for testing the DC resistance R of a lithium-ion battery at 25ºC is used to test the DC resistance of a lithium-ion battery at 0ºC, with the only difference being that the operating temperature is 0ºC.

[0065] Unless otherwise specified, the DCR mentioned in this application refers to the DC resistance of a lithium-ion battery at 10% state of charge (SOC).

[0066] 8. Electrochemical Impedance Spectroscopy (EIS) Test a) The preparation and lithium plating of the three-electrode battery are the same as those of the lithium-ion battery. In the preparation process of the lithium-ion battery, a copper wire is connected to the battery as a reference electrode. The negative electrode is lithium-plated at a current of 20μA for 6 hours. After the lithium plating is completed, the EIS is tested.

[0067] b) EIS test procedure: Connect the lithium-plated three-electrode battery to the Bio-Logic VMP3B electrochemical workstation manufactured by Biologie, France for testing. The test frequency range is 30mHz to 50kHz, and the amplitude is 5mV. After data acquisition, the data is analyzed using impedance complex plane plots to obtain the Rct data.

[0068] 9. Lithium-ion battery cycle expansion rate test The lithium-ion battery under test was placed at a test temperature of 45℃ and allowed to stand for 5 minutes. The initial thickness of the battery (PPG0 and MMC0) was recorded. Then, the lithium-ion battery was charged at a constant current of 0.7C to 4.45V, and then charged at a constant voltage of 4.45V to 0.05C. The battery thickness (PPG1 and MMC1) was recorded. After standing for 5 minutes, the battery was discharged at a constant current of 0.5C to 3.0V and allowed to stand for 5 minutes. This charge-discharge process was repeated 500 times. For the first 200 cycles, the battery thickness was recorded every 50 charge-discharge cycles. For the next 300-500 cycles, the battery thickness (PPGx and MMCx, where x represents the number of cycles) was recorded every 100 cycles. The residual capacity of each charge-discharge cycle was also recorded.

[0069] PPG Test: The PPG test uses a PPG soft-pack battery thickness gauge (manufactured by Shenzhen Aotomei Automation Technology Co., Ltd.) for automatic detection. The test procedure is to place the battery on the test plate of the instrument. During the test, the upper cover plate descends at a constant speed. The battery thickness PPGx is obtained through pressure sensing. The number of test cycles is indicated by x.

[0070] MMC Test: The MMC test uses a micrometer tester (manufactured by Mitutoyo, Japan, model: MDC-25SX) to measure the thickness at the positive electrode tab of the battery. Three points are measured (MMCax, MMCbx, MMCcx), where the letters a, b, and c correspond to different test positions, and the subscript x corresponds to the number of cycles in the test. MMCx = (MMCax + MMCbx + MMCcx) / 3, and MMC rebound = (MMCx - MMC0) / MMC0 × 100%.

[0071] The lithium-ion battery 45℃ cycle expansion rate is calculated based on the recorded battery thickness as follows: [PPGx / (Max(MMCax, MMCbx, MMCcx)) - 1] × 100%, where Max(MMCax, MMCbx, MMCcx) represents the maximum value among the three test points.

[0072] 10. 2C discharge capacity retention test After the lithium-ion battery was left to stand at 2°C for 5 minutes, it was charged at a constant current of 0.7C to 4.45V, then charged at a constant voltage of 4.45V to 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.5C to 3.0V, left to stand for 5 minutes. This charge-discharge process was repeated, discharging at 0.1C and recording the 0.1C discharge capacity of the lithium-ion battery, then discharging at 2C and recording the 2C discharge capacity. The 2C discharge capacity retention rate of the lithium-ion battery was calculated using the following formula: 2C discharge capacity retention rate = 2C discharge capacity / 0.1C discharge capacity × 100%.

[0073] Test Results [Table 1] Note: In Table 1, the half-width at half-maximum (WHM) of peak A in each example and comparative example is 0.1°, and the WHM of peak 101 is 0.3°; the thickness of the negative electrode active material layer is 30 μm, and the weight of the negative electrode active material layer per unit area is 0.003 g / cm³. 2 .

[0074] As shown in Examples 1-12, when the negative electrode active material layer satisfies 0.1 ≤ SA / S002 ≤ 0.3, the specific capacity of the lithium-ion battery can be significantly improved, the cycle expansion rate after 200 cycles can be significantly reduced, and the DC resistance value at 0°C can be reduced. The reduction in the cycle expansion rate after 200 cycles indicates that the lithium-ion battery has improved cycle performance, and the reduction in the DC resistance value at 0°C indicates that the lithium-ion battery has improved kinetic performance. Therefore, the lithium-ion batteries of Examples 1-12 have improved cycle performance, kinetic performance, and high specific capacity. When the negative electrode active material layer satisfies 7000 ≤ SA ≤ 9000 and / or 25000 ≤ S002 ≤ 90000, the lithium-ion battery has even better overall performance.

[0075] In Comparative Example 1, the SA / S002 ratio is higher than 0.3, resulting in a lower specific capacity of the lithium-ion battery, a higher cycle expansion rate after 200 cycles, and a higher DCR value at 0℃. In Comparative Example 2, the SA / S002 ratio is lower than 0.1, resulting in a higher specific capacity of the lithium-ion battery, but also a very high cycle expansion rate after 200 cycles and a higher DCR value at 0℃.

[0076] [Table 2] Note: The remaining parameters in the embodiments in Table 2 are the same as those in Embodiment 2. As shown in Table 2, the following conditions must be met: the half-width at half maximum (WHM) of peak A is 0.1°–0.5°, the WHM of peak 101 is 0.3°–0.8°, 30 μm ≤ H ≤ 80 μm, 87 ≤ SA / H ≤ 300, and C is 0.003 g / cm³. 2 Up to 0.01 g / cm 2 and / or 1.0≤10 4 When ×C / H ≤ 1.7, it helps to further improve the impedance of lithium-ion batteries, the lithium deposition of negative electrode plates, and the specific capacity of lithium-ion batteries, which can further improve the cycle performance and kinetic performance of lithium-ion batteries.

[0077] [Table 3] Note: The remaining parameters in the embodiments in Table 3 are the same as those in Embodiment 15. Examples 26 to 39 describe the relationship between the particle size distribution, BET, and S004 / S110 ratio of the negative electrode active material layer and battery performance. As shown in Table 3, when a lithium-ion battery satisfies the following conditions: 1μm≤Dv10≤10μm, 3μm≤Dv50≤18μm, 8μm≤Dv90≤35μm, chromium content of 0.008%-0.02%, niobium content of 0.005%-0.009%, sulfur content of 0.001%-0.006%, and / or 10≤S004 / S110≤25, it helps to further improve the DC resistance of the lithium-ion battery at 25ºC, the lithium plating of the negative electrode sheet, and the high-rate (2C) discharge capacity retention, thereby further improving the cycle performance and kinetic performance of the lithium-ion battery.

[0078] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the present application, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. An electrochemical device comprising a negative electrode, the negative electrode including a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer including a negative electrode active material, the negative electrode active material comprising natural graphite, wherein, The negative electrode active material layer satisfies 0.1 ≤ SA / S002 ≤ 0.3, where SA is the peak area of ​​the A peak in the XRD pattern of the negative electrode active material layer with 2θ ranging from 42.4° to 43.6°, and S002 is the peak area of ​​the O02 peak in the XRD pattern of the negative electrode active material layer; the thickness of the negative electrode active material layer is H μm, and 133.3 ≤ SA / H ≤ 300; the weight of the negative electrode active material layer per unit area is C g / cm³. 2 , 0.004≤C≤0.

01.

2. The electrochemical device according to claim 1, wherein, 7000≤SA≤9000 and / or 25000≤S002≤90000.

3. The electrochemical device according to claim 1, wherein, The half-maximum width of peak A is 0.1° to 0.5°.

4. The electrochemical device according to claim 1, wherein, In the XRD pattern of the negative electrode active material layer, there is a 101 peak in the range of 43.6° to 46.6° at 2θ, where 0.015≤S101 / S002≤0.035, and S101 is the peak area value of the 101 peak; and / or the half width at half maximum (WWHM) of the 101 peak is 0.3° to 0.8°.

5. The electrochemical device according to claim 1, wherein, The negative electrode satisfies at least one of conditions (a) to (d): (a) The negative electrode current collector is copper foil; (b) The negative electrode current collector contains chromium, and the chromium content is from 0.008% to 0.020% based on the mass of the negative electrode current collector; (c) The negative electrode current collector contains niobium, and the niobium content is from 0.005% to 0.009% based on the mass of the negative electrode current collector; (d) The negative electrode current collector contains sulfur, and the sulfur content is 0.001% to 0.006% based on the mass of the negative electrode current collector.

6. The electrochemical device according to claim 1, where 1.0 ≤ 10 4 ×C / H≤1.

7.

7. The electrochemical device according to claim 1, wherein, The negative electrode active material layer satisfies 10≤S004 / S110≤25, where S004 is the peak area value of the 004 peak in the XRD pattern of the negative electrode active material layer, and S110 is the peak area value of the 110 peak in the XRD pattern of the negative electrode active material layer.

8. The electrochemical device according to claim 1, wherein, The negative electrode satisfies at least one of conditions (g) to (h): (g) The specific capacity of the negative electrode active material is 360 mAh / g to 370 mAh / g; (h) The particle size of the negative electrode active material satisfies 1μm≤Dv10≤10μm, 3μm≤Dv50≤18μm, and 8μm≤Dv90≤35μm.

9. An electronic device comprising the electrochemical device according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Negative electrode comprising partly oriented graphite on corrent collector for rechargeable lithium battery, and rechargeable lithium battery

    EP3316378A1